The evaluation of hydraulic parameters in water distribution network using Epanet 2.0 (Case study: Comoro, Zone I, Timor-Leste) - Thalia de-Fatima Salsinha Soares (President University, 2021)
Abstract. In Timor-Leste, supplying clean water is the responsibility of Serviço de Água e Saneamento (SAS). The study area is in Zone I, locates in Comoro, Dili. The service area uses groundwater as the water source with two types of reservoirs; rectangular and cylinder. Objectives: This study aims to evaluate the existing condition of the water distribution network (WDN) in Zone I by using the Epanet 2.0 software. The development of the WDN begins with projecting the population with 10-year planning using the Geometric, Arithmetic, and Exponential methods. Method and results: The collection data is through observations in the study area as primary data. Secondary data is collecting SAS data, such as the map of water pipelines, piping data, pump data, reservoir data, and consumers' numbers. Processing data is the use of MS. Excel to calculate the population size, water demand, and identifying the pipelines of Zone I through QGIS. Followed by Epanet 2.0, with WDN data, the result is then evaluated with the Regulation of the Minister of Public Works No. 18 Year 2007 (No.18/PRT/M/2007). Conclusion: The results show that the WDN in Zone I have met the pressure requirement from No.18/PRT/M/2007 with an average flow of 19.57 litres/second. However, velocity still needs improvements since it did not meet the criteria; it suggests adding pump stations and reservoirs where the velocity did not meet the criteria. For the projection year in 2030, the estimated population is 26,057, with an average daily total water requirement of 48.46 litres/second.